Modeling the Effects of the Circadian Clock on Cardiac Electrophysiology. (February 2013) - Fotiadis, Panagiotis; Forger, Daniel B.
An internal circadian clock regulates the electrical activity of cardiac myocytes controlling the expression of potassium channel interacting protein–2 (KChIP2), which is a key regulator of cardiac electrical activity. Here, we examine how the circadian rhythm of KChIP2 expression affects the dynamics of human and murine ventricular action potentials (APs), as well as the intervals in the equivalent electrocardiograms (ECGs) reflecting the duration of depolarization and repolarization phases of the cardiac ventricular APs (QRS and QT intervals), with mathematical modeling. We show how the internal circadian clock can control the shape of APs and, in particular, predict AP, QRS, and QT interval prolongation following KChIP2 downregulation, as well as shortening of AP, QRS, and QT interval duration following KChIP2 upregulation. Based on the circadian expression of KChIP2, we can accurately predict the circadian rhythm in cardiac electrical activity and suggest the transient outward potassium currents as the key current for circadian rhythmicity. Our modeling work predicts a smaller effect of KChIP2 on AP and QT interval dynamics in humans. Taken together, these results support the role of KChIP2 as the key regulator of circadian rhythms in the electrical activity of the heart; we provide computational models that can be used to explore circadian rhythms in cardiac electrophysiology and susceptibility to arrhythmia.